Microfinance: A Powerful Tool for Social Transformation, Its Challenges, and Principles - Sharma, Puspa Raj (Journal of Nepalese Business Studies, 2006)
This paper attempts to explore the role and importance of microfinance in reducing poverty by generating the income of the poor. Microfinance has been emphasized for poverty reduction in developing countries through executing dual activities such as collection of domestic saving and investment of small loan. In this connection, this paper suggests microfinance practitioners and MFI to follow certain principles for making the microfinance services more sustainable in the long run and sheds light on the problems and challenges of microfinance.Journal of Nepalese Business Studies Vol.1(1) 2004 pp.69-74